The Evolutionary Origins of Cooperation in the Hominin Lineage: A Critique of Boyd and Richerson's Cultural Group Selection Account. Issue 5 (December 2021) - Neal, Jacob P.
Abstract : The origin of human cooperation poses an evolutionary puzzle. In order for cooperation to evolve, our Pleistocene ancestors must have overcome the free rider problem, in which noncooperators reap the benefits of cooperation without paying the costs. Cultural group selection accounts offer a potential solution to this problem. In this article, I evaluate Boyd and Richerson's influential account. I argue that it cannot explain the evolutionary origins of human cooperation because it presupposes cooperative behaviors among our Pleistocene ancestors. Although Boyd and Richerson's account may explain the expansion of cooperation in hominin evolution, it cannot explain how cooperative behaviors first emerged.